The Hierarchy of Human Needs Through the Main Character in the Danish Girl Movie - Komang Wulandari Oktapiana; I Made Perdana Skolastika (Prologue: Journal on Language and Literature, 2022)
A character is an essential element in a literary work, especially a movie. Each character in a story has a different mental or psychological condition. This study aims to analyze the hierarchy of human needs contained in the main character named Einar Wegener in The Danish Girl movie directed by Tom Hopper. The theory used in this movie is the psychological theory by Abraham Maslow. The method used in this study is a qualitative descriptive method. The results of this study show that the main character, Einar Wegener, succeeded in fulfilling his four basic needs consisting of physiological needs, security needs, love and belongingness, and self-esteem. However, there is one need that he failed to fulfill, namely self-actualization.